2017
DOI: 10.1016/j.pharep.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin ameliorates hepatic fibrosis in high fat diet induced non-alcoholic fatty liver disease by regulation of FoxO1 mediated pathway

Abstract: As per the previous studies, a potential therapy for NAFLD may be the one with multi-faceted actions on insulin resistance, oxidative stress, inflammation and fibrosis. This study demonstrates the efficiency of Esculetin in improving liver fibrosis in HFD induced NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Benzbromarone is associated with fulminant hepatitis, liver failure, and rare cases of serious liver toxicity [ 48 , 49 , 50 ]. Previous studies have showed that the hepatotoxicity of esculetin is negligible [ 51 , 52 , 53 , 54 ]. In this study, hepatic damage was assessed by through AST and ALT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Benzbromarone is associated with fulminant hepatitis, liver failure, and rare cases of serious liver toxicity [ 48 , 49 , 50 ]. Previous studies have showed that the hepatotoxicity of esculetin is negligible [ 51 , 52 , 53 , 54 ]. In this study, hepatic damage was assessed by through AST and ALT activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that esculetin has some biological and pharmacological activities, including anti-oxidative ( 16 , 17 ), anti-inflammatory ( 18 ), anti-viral ( 19 ), anti-asthmatic ( 20 ), and anti-tumor effects ( 21 , 22 ). As an anti-inflammatory drug, esculetin can exert therapeutic effects on several inflammatory diseases, such as hepatic fibrosis ( 23 ), arthritis ( 24 ), and atopic dermatitis ( 25 ). Previous studies have also reported that esculetin inhibits T cell activation without suppressing IL-2 production or IL-2 receptor expression ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sections were stained with hematoxylin and eosin (H&E). Furthermore, sections were subjected to Masson's trichrome staining [23] or Sirius red staining to evaluate liver fibrosis [24].…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Chronic high fat diet (HFD) feeding is used as an efficient tool to simulate clinical NAFLD and associated hepatic fibrosis [14]. Long-term HFD feeding induces the pathological changes including visceral obesity, inflammation, hyperlipidemia and hepatic fibrosis which are similar to that of the human NAFLD [15]. It has been reported that all the rats developed perisinosodial fibrosis after 24 weeks' HFD feeding [14].…”
Section: Introductionmentioning
confidence: 99%